(untitled) (Research, Society and Development, 2020)
Tertiary Care or High Complexity is understood to be a set of highly specialized services, with high-density and high-cost technological resources. The objective is to evaluate the highly complex services of reference to assistance to people living with HIV / AIDS in Rio Grande do Norte. This work consists of a descriptive and analytical research developed in the services of high complexity in HIV / AIDS in Rio Grande do Norte, consisting of reference Hospitals of Infectocontagious Diseases, which took the codenames HGT and HRF. Secondary data from the reports issued by the institutions and the Ministry of Health were used, based on the Qualiaids Questionnaire (version 2017). Only the domains categorized in standard 0 (unsatisfactory) and discussed according to Bardin’s Content Analysis (2009) were discussed. The research was approved by the Research Ethics Committee - CEP of the State University of Rio Grande do Norte - UERN under Opinion: 2,567,260. From the analysis of the 76 indicators present in Qualiaids, the HGT had 28 indicators classified in standard 0, being 12 of assistance, 07 of management and 09 of resources, while, the HRF had 17 indicators, being 06 of assistance, 06 of management and 05 resources. Similar realities are seen in both high complexity hospitals in the state, however, facing difficulties related to assistance, resources and management, however, according to the evaluation of the indicators, HRF is better structured in relation to HGT.